The f-factor, neutron, gamma radiation and proton shielding competences of glasses with Pb or Pb/Bi heavy elements for nuclear protection applications. Issue 17 (1st December 2020) - Rammah, Y.S.; Olarinoye, I.O.; El-Agawany, F.I.; El-Adawy, A.; Yousef, El Sayed
Abstract: In this article, proton, neutron, and gamma-ray shielding competences of six glasses with PbO or PbO/Bi2 O3 heavy metal oxides namely as Glass 1 to Glass 6 have been investigated via WinXcom and EXABCal computer codes. The maximum values of μ m were equal to 50.6, 53.06, 72.51, 80.67, 99.54, and 102.35 cm 2  g -1 at 0.015 MeV for Glass 1 to Glass 6, respectively. The μ m of the glass's trend in ascending order for Glass 1 to Glass 6. Results of HVL and MFP of the glass's were trend in descending order for Glass 1 to Glass 6. The Z e f f of glasses varied from 14.49 (1.5 MeV) to 37.78 (0.1 MeV) and from 43.93 (2 MeV) to 65.62 (0.02 MeV) for Glass 1 and Glass 6, respectively. The f -factor of Glass 5 and Glass 6 was maximum for throughout the energy spectrum. The buildup factors are low and grow with the penetration depth rapidly up to the maximum depth of 40 mfp. The values of Σ R were varied from 0.0947 to 0.1155 cm −1 for Glass1 to Glass 6, respectively. Glass 2 and Glass 6 are preferred fast neutron shield when compared with ordinary concrete, water, and graphite. Generally, the molar concentration of PbO or PbO + Bi2 O3 improved the shielding capacity of the investigated glasses.